The Growth Optimization of Pak Choy (Brassica rapa L. var. chinensis) in Household-Scale Aquaponics System - Priadi, Dody; Wibowo, Heru; Mulyaningsih, Enung Sri (Jurnal Biodjati, 2019)
The growth of Pak Choy (Brassica rapa var. chinensis) using nutrients from catfish â€œSangkuriangâ€ (Clarias gariepinus) wastes was investigated in the household scale aquaponics systems by comparing the growth parameters value among the grow beds.Â The growth parameter ofÂ Pak Choy was fresh weight, leaf number, and leaf area. Meanwhile, catfish growth parameters were body weight and length, and feed conversion ratio (FCR). The experiments were arranged in a Completely Randomized Design (CRD)Â with 4 treatments and 3 replications. The data wereÂ analyzed using Analysis of Variance (Anova) followed by Duncan Multiple Range Test (DMRT) at 95% level of significant The result of the study showed that there were not significantly different in the growth parameter of Pak Choy among the grow bedsÂ in the vertical system. However, those in grow bedsÂ â€œÃ„â€ were significantly higher than the rest of the grow bedsÂ in the horizontal aquaponics system. In general, all the growth parameter of Pak Choy in the vertical system was higher than in the horizontal one, although, it was not statistically significantly different. Nevertheless, the horizontal aquaponics system gave better results in the body weight and FCR of catfish.Â 